The supramolecularly complexes of calix[4]arene derivatives toward favipiravir antiviral drug (used to treatment of COVID-19): a DFT study on the geometry optimization, electronic structure and infrared spectroscopy of adsorption and sensing - Yüksel, Numan; Köse, Ahmet; Fellah, Mehmet Ferdi (Springer Science and Business Media B.V., 2021)
While the world is in search of a vaccine that can cure COVID-19 disease, favipiravir is the most commonly used antiviral drug in the treatment of patients during the pandemic process. In this study, we investigated the host–guest interaction between the popular supramolecule calix[4]arene derivatives and the favipiravir drug by using the DFT (Density Functional Theory) method. The B3LYP hybrid method and 6-31G (d,p) basis set were utilized to determine the optimized structures of the host and guest molecules and their complexes. The negative adsorption energy (∆E) and adsorption enthalpy (∆H) calculated for the complexes formed between calix[4]arene compounds and favipiravir drug molecule mentioned that adsorption of favipiravir molecule was an exothermic process on calix[4]arene structures. On the other hand, among the calixarene derivatives in the study, Gibbs free energy change (∆G) value for the adsorption was only negative on calix[4]arene4 molecule. The infrared spectroscopy (IR) calculations were performed by examining the C=O, O–H and NH2 vibrational frequencies to see the adsorption behavior in the favipiravir-calix[4]arene complex. After adsorption of the favipiravir molecule, HOMO–LUMO gap values decreased significantly for the structures and therefore electrical conductivity increased proportionally. In addition, sensor response factors, Fermi energy levels and workfunction changes of calix[4]arene derivatives were calculated and examined. Charge transfer between the four calix[4]arene compounds and the favipiravir molecule has occurred after adsorption. This attributes that calix[4]arene derivatives can be used as a well-suited favipiravir sensor (electronic and workfunction) and adsorbent at room temperature. Based on the calculations made to see the solvent effect on the adsorption of favipiravir it was determined that it did not affect the interaction between the drug molecule and the calix[4]arene compound too much and the adsorption energy turned into a slightly less negative value.
Keywords: Adsorption; Calix[4]arene; Detection; DFT; Favipiravir